Privatization, Political Risk and Stock Market Development in Emerging Economies - Enrico C. Perotti; Pieter van Oijen (Tinbergen Institute, 1999)
This paper investigates whether privatization in emerging economies has a significant indirect effect on local stock market development through the resolution of political risk. We argue that a sustained privatization program represents a major political test that gradually resolves uncertainty over political commitment to a market-oriented policy as well as to regulatory and private property rights. We present evidence suggesting that progress in privatization is indeed correlated with improvements in perceived political risk. Our analysis further shows that changes in political risk in general tend to have a strong effect on local stock market development and excess returns in emerging economies. We conclude that the resolution of political risk resulting from successful privatization has been an important source for the rapid growth of stock markets in emerging economies.
Keywords: G18; F30; 330; Emerging economies; Privatization; Political risk; Stock markets; Privatisierung; Schwellenländer; Aktienmarkt; Kapitalmobilität; Länderrisiko; Welt